2020
DOI: 10.1002/bit.27373
|View full text |Cite
|
Sign up to set email alerts
|

Current genetic engineering strategies for the production of antihypertensive ACEI peptides

Abstract: Hypertension is a major and highly prevalent risk factor for various diseases. Among the most frequently prescribed antihypertensive first‐line drugs are synthetic angiotensin I‐converting enzyme inhibitors (ACEI). However, since  their use in hypertension therapy has been linked to various side effects, interest in the application of food‐derived ACEI peptides (ACEIp) as antihypertensive agents is rapidly growing. Although promising, the industrial production of ACEIp through conventional methods such as chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 128 publications
1
5
0
Order By: Relevance
“…The N-and-C-termini of the 4 peptides identified in this study were similar to those previously reported for ACE-inhibitory peptides ( 55 57 ). The properties of MELVLK and TELVLK are also consistent with the view proposed by Fujita et al, that the positive charge on the C-terminal basic residue or basic residue (R/K) contributes greatly to the inhibitory potency ( 58 , 59 ). In the peptide sequences we studied, the content of hydrophobic amino acids is very high.…”
Section: Discussionsupporting
confidence: 89%
“…The N-and-C-termini of the 4 peptides identified in this study were similar to those previously reported for ACE-inhibitory peptides ( 55 57 ). The properties of MELVLK and TELVLK are also consistent with the view proposed by Fujita et al, that the positive charge on the C-terminal basic residue or basic residue (R/K) contributes greatly to the inhibitory potency ( 58 , 59 ). In the peptide sequences we studied, the content of hydrophobic amino acids is very high.…”
Section: Discussionsupporting
confidence: 89%
“…The induction of hypertension is related to a complex interplay of environmental, hereditary, and other internal or external factors, including increased cardiac output or systemic vascular resistance, excessive activation of sympathetic nervous systems, vascular remodeling, excessive release of endothelins, enhancement of the renin–angiotensin system (RAS), and abnormal glomerular capillary filtration function [ 3 , 5 , 6 ]. The RAS is a major factor controlling changes in blood pressure, which is regulated by renin and mediated by the vital stress hormone angiotensin II (AngII) to lead to powerful vasoconstrictive actions [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main function of the angiotensin-converting enzyme (ACE) is to catalyze the conversion of angiotensin I (AngI) into AngII, and it is considered to be the core enzyme in the RAS [ 9 , 10 ]. Therefore, ACE inhibitors (ACEIs) are increasingly becoming the main hypertension treatment drugs [ 6 ]. Initial ACEIs were separated and extracted from snake venom, and their potency was unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in recent years, the research on bioactive peptides has gradually become active, and the prospects are becoming more and more promising. The current research and development directions of BAPs are roughly as follows: (1) The discovery of new active peptides, structural analysis, and activity research, and so forth 19 ; (2) Development of targeted enzymatic hydrolysis technology for protein preparation of active peptides, including high‐efficiency and specific enzyme‐producing strains breeding, research on the joint action mechanism of complex enzyme systems, improvement of enzymatic hydrolysis technology, and so forth 20 ; (3) Separation of functional peptides and development of analytical techniques, especially high‐sensitivity, simple, and easy target peptide activity analysis and detection systems and analytical techniques 21 ; (4) Research on functional biological evaluation of peptides 22 ; (5) Development of bioactive peptide medicines and functional foods 23 ; (6) Engineering research on low‐cost, high‐purity, and mass production of bioactive peptides 24 ; (7) Application research of bioengineering technology in the preparation of active peptides, such as protein engineering, 25 enzyme engineering, 26 genetic engineering, 27 cell culture technology, 28 and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Separation of functional peptides and development of analytical techniques, especially high-sensitivity, simple, and easy target peptide activity analysis and detection systems and analytical techniques 21 ; (4) Research on functional biological evaluation of peptides 22 ; (5) Development of bioactive peptide medicines and functional foods 23 ; (6) Engineering research on low-cost, highpurity, and mass production of bioactive peptides 24 ; (7) Application research of bioengineering technology in the preparation of active peptides, such as protein engineering, 25 enzyme engineering, 26 genetic engineering, 27 cell culture technology, 28 and so forth.…”
mentioning
confidence: 99%